The correlation between the hip rotational range of motion and the medicine ball rotational throw ability of youth baseball players - Chang, H. Y.; Chiu, C. W.; Lo, C. L. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: A baseball player needs adequate hip joint mobility to perform throwing or hitting techniques. The hip joint is located at the core of the human body and also connects the lower leg and trunk which allow the force transfer from the lower extremities to the upper body and upper extremities. The purpose of this study was to understand the correlation between the hip rotational range of motion and the medicine ball rotational throw ability of youth baseball players. METHODS: Thirty-six Taiwan national WBSC U18 baseball players (mean height 179.9 ± 7.0 cm, mean weight 80.8 ± 10.8 kg, mean age 17.1 ± 0.6 years) participated in this study. The Goniometer was used to measure the hip internal and external rotation range of motion (ROM) of the leading leg (non-dominant side) and axial leg of the players. All participants also hold a smart medicine ball (A2P Ballistic Ball, abbreviation: MBP) with a sensor built into the ball to perform medicine ball turning and throwing movements for a total of 2 repetitions, and collected the values of MBP peak velocity, average velocity, and power. The Pearson correlation coefficient was used to analyze the relationship between medicine ball rotation throwing parameters and hip internal and external rotation ROM. The Paired-T Test was used to compare the difference between leading and axial leg in hip internal and external rotation. RESULTS: There are significantly fewer degrees in the leading leg (25.5±5.3°) than axial leg (34.4±6.0°) for hip Internal rotation ROM (p< .05), and there was no significant difference in the rest. CONCLUSION: The large hip external rotation ROM of the leading leg for baseball players may negatively affect the transmission of the power output when performing the medicine ball rotation throwing movement for the baseball players.